Correction: XSnS3 (X = Ga, In) monolayer semiconductors as photo-catalysts for water splitting: a first principles study. Issue 31 (28th July 2022) - Naseri, Mosayeb; Salahub, Dennis R.; Vu, Tuan V.; Zakaryae, Haman
Abstract : Correction for 'XSnS3 (X = Ga, In) monolayer semiconductors as photo-catalysts for water splitting: a first principles study' by Mosayeb Naseri et al., J. Mater. Chem. C, 2022, ; https://doi.org/10.1039/d2tc01613c .